Theoretical description of charge transport in disordered organic semiconductors (Phys. Status Solidi B 3/2014). Issue 3 (7th March 2014) - Baranovskii, S. D.
<x xml:space="preserve">Abstract</x> Organic disordered semiconductors (ODS) dominate already today the electrophotographic image recording on the industrial scale and are becoming more and more important for applications in light‐emitting diodes, in field‐effect transistors, in solar cells and other devices. Charge transport properties of ODS are decisive for all these applications. Many transport properties of ODS were reviewed by Heinz Bässler [Phys. Status Solidi B 175, 15 (1993)], who concluded that charge transport in single‐component and multi‐component ODS is due to incoherent tunneling (hopping) of carriers via randomly distributed localized states with a Gaussian energy distribution. The conclusion was based on the comparison between experimental data and the results of computer simulations. Theoretical research on charge transport in ODS is still often based on numerical modeling with empirical fitting of the results by analytical expressions using several fitting parameters. Such empirical fitting does not bring, however, a fundamental understanding of the underlying physical processes. In the Review Article by S. D. Baranovskii (pp. 487–525) the emphasis is therefore put on the development of analytical theories for the description of charge transport in ODS. It is shown that wellapproved theoretical tools, used since decades for the description of hopping transport in inorganic disordered materials, are capable to account for the pronounced dependences of carrier mobility on the temperature, on the applied electric field, on the concentration of localized states, and on the concentration of charge carriers also in ODS. Among such tools are the percolation theory, the concept of the transport energy, the concept of the effective temperature and some other approaches reviewed by Baranovskii. It looks almost miraculous that the application of these methods to a model, in which complicated morphology of a disordered organic system is replaced by a set of randomly distributed point‐like localization centers with Gaussian distribution of energies, yields a description of almost all experimentally observed features related to charge transport in ODS. S. D. Baranovskii is indebted to Jan Oliver Oelerich for preparing the design for the Front Cover. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>